PENGARUH STRUKTUR KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN DAN LEGAL ORIGIN TERHADAP MANAJEMEN LABA - Cahyo Indraswono (Jurnal Akuntansi Bisnis, 2015)
The objective of the research are to find out empirical evidence about the effect of institutional ownership structure, firm size and legal origin on earnings management by companies Asia listed in New York Stock Exchange (NYSE). The role of earnings in compensation contracts and performance appraisal may be driving the emergence of earnings management. Measures of earnings management can be minimized by monitoring the management using the proportion of institutional ownership in the company. The complexity of the business and reputation of the company can raise the size of the company as part of the increasing influence of information asymmetry and earnings management. For companies listed on foreign stock markets, the legal system of the country of origin (legal origin) might impact on earnings management of the company.Companies in countries with civil law legal origin have higher earnings management than firms in countries with common law legal origin. Earnings management is measured using the modified Jones model of discretionary accruals as a proxy for earnings management. This study use 50 companies Asia listed in NYSE as sample, during the 2009-2011 year period of observation. Statistical test using multiple regression. This study obtained evidence that institutional ownership structure and firm size significantly negative effect on earnings management. While legal origin did not affect effect on earnings management of the company. This happens because the NYSE stock market is in a country with strong investor protection so that the legal origins of the Asia companies do not affect earnings management action.